Beyond suspicion? the Singapore judiciary - Seow, Francis T. (Strategic Information and Research Development Centre, 2008)
Beyond Suspicion? The Singapore Judiciary is essential to understanding the true nature of human rights abuses in that country. Particularly thorough are the chapters dealing with the use of civil defamation suits through the courts by ruling party leaders against political critics.